Influence of the Buccal Bone Crest Width on Peri-Implant Hard and Soft Tissues Dimensions: A Histomorphometric Study in Humans. Issue 4 (August 2018) - Omori, Yuki; Iezzi, Giovanna; Perrotti, Vittoria; Piattelli, Adriano; Ferri, Mauro; Nakajima, Yasushi; Botticelli, Daniele
Abstract : Objective: To histologically evaluate hard and soft tissues adaptation at screw-shaped devices installed at recipient sites in the distal segments of the alveolar edentulous ridge prepared with a buccal bone width of 1 or 2 mm. Material and Methods: Sixteen volunteers received 2 nonsubmerged titanium implants each; after 3 months, biopsies were obtained and processed for histology. The distances between implant shoulder (IS), top of the bony crest (C), coronal level of osseointegration (B), peri-implant mucosa (PM), and apical extension of the junctional epithelium (aJE) were measured. Results: There were no significant statistically differences between test and control sites regarding IS-C, IS-B, PM-IS, PM-B, PM-aJE, aJE-B measurements. The horizontal bone resorption 1 mm below IS was 0.3 ± 0.3 and 1.0 ± 0.7 mm at the test and control sites, respectively. This difference was statistically significant. Conclusions: Similar hard and soft tissues dimensions were observed in both groups. However, a higher horizontal bone resorption was seen at the control sites. Nonsubmerged implant installation should be performed when a 1 mm buccal bony crest width is present so as to limit the horizontal bone resorption.